The Power of Female Rage: Challenging the Feminine Mystique - Yuzadarman, Talitha Ulima; Istiani, Imas (Journal of Language and Literature Studies, 2025)
This study analyzes the representation and critique of domesticity through female rage in Rachel Yoder’s novel Nightbitch. The two primary topics of the study are (1) how domesticity is depicted in the novel and (2) how the female protagonist challenges traditional domestic roles through the expression of rage. This qualitative study employs textual analysis within a feminist literary framework, drawing on Judith Butler’s theory of performativity and Betty Friedan’s concept of the feminine mystique. This study is important as it examines the societal pressures on women in domestic roles and investigates how female rage serves as a means of resistance and identity reconstruction. The findings indicate that domesticity is represented as a socially constructed identity influenced by patriarchal norms, which limits the protagonist to the roles of mother and wife. The protagonist redefines womanhood and motherhood through symbolic acts, including naming herself “Nightbitch,” transforming into a dog, and expressing suppressed rage, thereby redefining the womanhood and motherhood on her own terms. These findings demonstrate that female rage functions not as a destructive force but as a catalyst for liberation and identity reconstruction. Beyond the novel itself, the study highlights how contemporary feminist literature reclaims women’s anger as a resource for challenging gender expectations and expanding the discourse on motherhood and femininity.